2022
DOI: 10.1002/smll.202203674
|View full text |Cite
|
Sign up to set email alerts
|

Long Shelf‐Life Efficient Electrolytes Based on Trace l‐Cysteine Additives toward Stable Zinc Metal Anodes

Abstract: The unstable anode/electrolyte interface (AEI) triggers the corrosion reaction and dendrite formation during cycling, hindering the practical application of zinc metal batteries. Herein, for the first time, l‐cysteine (Cys) is employed to serve as an electrolyte additive for stabilizing the Zn/electrolyte interface. It is revealed that Cys additives tend to initially approach the Zn surface and then decompose into multiple effective components for suppressing parasitic reactions and Zn dendrites. As a conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…S5 (ESI†) presents the adsorption energy of these additives on the Zn (0001) surface. As expected, these solvents both delivered lower adsorption energy than H 2 O (−0.22 eV), 48 suggesting their higher affinity to the Zn surface, which enables them to replace the partial H 2 O in the EDL structure. Based on the above analysis, we concluded that the major role of these solvents is to regulate the EDL structure instead of the bulk properties of electrolytes (Fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…S5 (ESI†) presents the adsorption energy of these additives on the Zn (0001) surface. As expected, these solvents both delivered lower adsorption energy than H 2 O (−0.22 eV), 48 suggesting their higher affinity to the Zn surface, which enables them to replace the partial H 2 O in the EDL structure. Based on the above analysis, we concluded that the major role of these solvents is to regulate the EDL structure instead of the bulk properties of electrolytes (Fig.…”
Section: Resultssupporting
confidence: 63%
“…Recently, the shelf life of electrolytes has also attracted attention due to the required long storage period of practical products. 48 Therefore, Sul/ZnSO 4 solutions were aged for 12 months and then employed as electrolytes to assemble Zn|Cu half cells. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6f). [40][41][42][43][44][45] The results conrm the promoted electrochemical performance by the EC additive for not only the Zn anode but also full cells.…”
Section: Resultsmentioning
confidence: 84%
“…α-V 2 O 5 has been frequently used as a cathode material in the aqueous ZIBs. [120][121][122] It has been confirmed that during the discharge process of aqueous ZIBs, the hydrated Zn-ions will be inserted into the interlayer space of V 2 O 5 , during which the hydration sheath of Zn-ions plays a critical role in reducing the electrostatic interactions between Zn-ions and the host structure and facilitating the Zn-ions diffusion. However, the structure evolution of α-V 2 O 5 during Zn-ions insertion is ambiguous, which is attributed to the acidic environment of the electrolyte.…”
Section: Zinc-ion Batteriesmentioning
confidence: 98%